Horizon, sea, sound : Caribbean and African women's cultural critiques of nation - Davis, Andrea, 1963- (Critical insurgencies., 2022)
"This book imagines new reciprocal relationships beyond the competitive forms of belonging suggested by the nation-state. The book employs the tropes of the horizon, sea, and sound as a critique of nation-state discourses and formations"--